2009
DOI: 10.1016/j.envres.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of urinary cadmium on cardiovascular fitness as measured by VO2 max in white, black and Mexican Americans

Abstract: THE EFFECT OF URINARY CADMIUM ON CARDIOVASCULAR FITNESS AS MEASURED BY VO2 MAX IN WHITE, BLACK AND MEXICAN AMERICANS. ________________________________________________________________________Heartley Egwuogu: Institute of Public Health Georgia State University Atlanta Georgia. Context:Cadmium is an important predictor of lung function, including forced vital capacity, forced expiratory volume and peak flow. Current evidence supports the notion that cadmium may be an important risk factor for cardiovascular fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…However, cadmium remains a concern because of evidence indicating toxicity at the current levels of environmental exposure. For example, even at the reduced recent levels of exposure, cadmium has been related to cardiovascular, bone, and kidney disease in studies of NHANES 1999–2008 data (Egwuogu et al 2009; Gallagher et al 2008; Navas-Acien et al 2004, 2005, 2009; Peters et al 2010; Tellez-Plaza et al 2008, 2010), supporting the need to further reduce cadmium exposure. Because the epidemiologic evidence available is mostly cross-sectional, prospective epidemiologic studies are needed to understand the health consequences of cadmium exposure and to evaluate the adequacy of current food and environmental safety standards.…”
Section: Resultsmentioning
confidence: 99%
“…However, cadmium remains a concern because of evidence indicating toxicity at the current levels of environmental exposure. For example, even at the reduced recent levels of exposure, cadmium has been related to cardiovascular, bone, and kidney disease in studies of NHANES 1999–2008 data (Egwuogu et al 2009; Gallagher et al 2008; Navas-Acien et al 2004, 2005, 2009; Peters et al 2010; Tellez-Plaza et al 2008, 2010), supporting the need to further reduce cadmium exposure. Because the epidemiologic evidence available is mostly cross-sectional, prospective epidemiologic studies are needed to understand the health consequences of cadmium exposure and to evaluate the adequacy of current food and environmental safety standards.…”
Section: Resultsmentioning
confidence: 99%
“…29 An inverse association between urinary cadmium levels and level of cardiovascular fitness assessed by volume of oxygen consumed at submaximal activity was demonstrated in participants of NHANES 1999-2000. 30 There is paucity of data studying associations between other heavy metals and cardiovascular morbidity and mortality. Navas-Acien et al demonstrated an association of urinary cadmium, tungsten, and antimony with PAD in a smaller subsample derived from NHANES 1999-2000.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, cadmium exposure has substantially decreased during the last decades, in part related to reductions in smoking [ 34 ]. Cadmium exposure, however, remains an important concern, because even at the currently reduced levels of exposure, cadmium has been related to cardiovascular, bone, and kidney disease in studies of the US National Health and Nutrition Examination Survey (NHANES) 1999 to 2008 data [ 35 - 41 ]. In epidemiologic studies, cadmium concentrations in blood and urine are established biomarkers of cadmium exposure and internal dose [ 33 , 42 ].…”
Section: Reviewmentioning
confidence: 99%